Exposing Company Value's Hidden Factors: The Effect of Revaluing Fixed Assets and Important Determinants - Permata, Irma Sari; Baharuddin, Gunawan (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
AbstractThis study examines the impact of the Investment Opportunity Set, Liquidity, Ownership Structure, and Company Size on Company Value in firms conducting Fixed Asset Revaluations on the Indonesian Stock Exchange (2015-2022). Using a quantitative approach with hypothesis testing, the research analyzes 211-panel data samples through multiple linear regression. Findings reveal that Ownership Structure does not significantly affect Company Value, while the Investment Opportunity Set, Liquidity, and Company Size have a partial influence. The study contributes to financial literature by highlighting the role of fixed asset revaluation in modifying company value. Additionally, it provides insights for policymakers in shaping revaluation policies and serves as a key reference for businesses considering asset revaluation.